The Physicochemical Characteristics of Palado Seed Flour (Aglaia sp.) and Its Potential Use as a New Alternative Flour in Indonesia - Syamsul Rahman; Salengke Salengke; Abu Bakar Tawali; Meta Mahendradatta (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2022)
Flour is one of the main energy sources for humans and an important ingredient in food processing, for use as fillers, thickeners, gel, film forming and adhesives. Therefore, this study aimed to analyze the physicochemical characteristics of palado seed flour (Aglaia sp.) including proximate analysis and chemical properties comprising energy, carbohydrates, water, and protein, content, as well as dietary fiber, starch, amylose and amylopectin. Furthermore, the physical properties including yield, particle size, degree of whiteness, paste clarity, gel strength, swellability and water absorption, as well as the potential use of palado flour (Aglaia sp) in food processing were analyzed. The study was conducted with a method comprising two stages, namely pre-treatment including processing palado fruit into seeds, drying, and extracting flour, as well as proximate analysis of the physicochemical characteristics. The results showed energy content of 396.14 kcal/100 g, carbohydrates 69.78%, water content 7.53%, protein 9.59%, fat 8.74%, dietary fiber 4.02. %, ash 4.36%, starch 41.31%, amylose 5.68% and amylopectin content 35.63%. Meanwhile, the physical characteristics include the yield of 84.21% with a particle size of 60 mesh, degree of whiteness 29.27%, paste clarity 29.7%, gel strength 109.96 gf, swelling power 0.4%, and water absorption 133.72 %. Based on the results, palado flour has high potential to be developed as the main or alternative ingredient in bread and noodle processing, such as durian and jackfruit seed flour.